CD36 promotes iron accumulation and dysfunction in CD8 T cells via the p38-CEBPB-TfR1 axis in earlystage hepatocellular carcinoma - Yifei Qin; Fei Huo; Zhuan Feng; Jialu Hou; Yaxin Ding; Quancheng Wang; Yu Gui; Ziwei Yang; Jiali Yang; Gang Zhou; Ling Li; Jianli Jiang; et al. (Clinical and Molecular Hepatology)
Background/Aims The identification of factors that lead to CD8+ T cell dysfunction within the tumor microenvironment (TME) holds great promise for the development of innovative immunotherapies. However, the mechanisms underlying the exhausted phenotype of CD8+ T cells infiltrating early-stage hepatocellular carcinoma (HCC) tumors remain unclear. Methods Single-cell RNA sequencing was performed using a murine HCC model. Flow cytometry and additional experimental approaches were employed to investigate the mechanisms of CD8+ T cell exhaustion. Results CD8+ T cells infiltrating early-stage HCC exhibited a functionally exhausted phenotype, which escalated with HCC progression. At early stages of HCC, the TME was characterized by significant iron accumulation. Moreover, tumor-infiltrating CD8+ T cells in murine HCC exhibited higher levels of intracellular ferrous iron compared to splenic CD8+ T. This excessive iron led to increased lipid peroxide levels and impaired the effector function of CD8+ T cells. Mechanistically, CD36 upregulated the iron uptake protein transferrin receptor 1 (TfR1) by mediating the activation of oxidized low-density lipoprotein (oxLDL)-p38-CEBPB axis. Depletion of CD36 in CD8+ T cells inhibited the upregulation of TfR1 and the increase of iron levels. Furthermore, constitutively activated nuclear factor erythroid 2-related factor 2 (NRF2) effectively suppressed lipid peroxidation, thereby preserving the effector functions of intratumoral CD8+ T cells and ultimately inhibiting tumor growth. Conclusions Our findings reveal a previously unidentified mechanism mediated by CD36 that regulates the progressive dysfunction of CD8+ T cells in early HCC TME and provide a potential novel therapeutic approach to restore T cell function.